Pelaksanaan Pembelajaran Seni Budaya (Tari) Di SMA Negeri 4 Kota Sungai Penuh Provinsi Jambi: Studi Deskriptif PBM Di Era New Normal - Wenda Yulyansi; Susmiarti Susmiarti (SENDRATASIK UNP, 2022)
This study aims to describe the implementation of cultural arts (dance) learning at SMAN 4 Sungai Penuh City, Jambi Province in the new normal era of covid-19. This type of research is qualitative research with a descriptive analysis approach. The main instrument in this study was the researcher himself, assisted by supporting instruments such as writing instruments and cameras. This type of data uses primary data and secondary data. Data collection techniques were carried out by observation, interviews, and documentation studies. The data analysis technique is done by collecting data, describing the data and concluding the data. The results showed that the planning made by the teacher, namely lesson plans, was relevant to the design of K13 because the topic of learning in K13 Class X IPA 2 SMA N 4 Sungai Full Semester two (even) was a dance tradition. The suitability of subject topics in K13 is the existence of KD and KD indicators following the expected learning of K13 objectives. The teacher uses the strategy of delivering material, assessment, and learning using the question and answer method. With this method, the authors found that students were less interested in participating in learning. As for the third meeting, the teacher must be able to use a demonstration strategy by giving an example to students on how to properly move traditional dances. The technique used by the teacher must also be more creative to attract the attention of students. The process of supporting the learning of arts and culture at SMA Negeri 4 Sungai Penuh is also not sufficient. The lack of facilities and infrastructure provided by schools also results in learning that is not carried out properly.